Insight change in psychosis: relationship with neurocognition, social cognition, clinical symptoms and phase of illness. (18th April 2013) - Quee, P. J.; van der, L.; Krabbendam, L.; de, L.; Cahn, W.; Wiersma, D.; van, N.; Pijnenborg, G. H. M.; Mulder, C. L.; Bruggeman, R.; Aleman, A.
<x xml:space="preserve">Abstract</x> Objective Impaired insight is an important and prevalent symptom of psychosis. It remains unclear whether cognitive disturbances hamper improvements in insight. We investigated the neurocognitive, social cognitive, and clinical correlates of changes in insight. Method One hundred and fifty‐four patients with a psychotic disorder were assessed at baseline (T0) and after three years (T3) with the Birchwood Insight Scale, the Positive And Negative Syndrome Scale, measures of neurocognition and social cognition. Linear regression analyses were conducted to examine to what extend neurocognition, social cognition, clinical symptoms and phase of illness could uniquely predict insight change. Subsequently, changes in these factors were related to insight change. Results Better neurocognitive performance and fewer clinical symptoms at baseline explained insight improvements. The additional effect of clinical symptoms over and above the contribution of neurocognition was significant. Together, these factors explained 10% of the variance. Social cognition and phase of illness could not predict insight change. Changes in clinical symptoms, but not changes in neurocognitive performance were associated with insight change. Conclusion Neurocognitive abilities may predict, in part, the development of insight in psychosis.